Two-Solid Deposition in Fluid Column using Immersed ‎Boundary-Lattice Boltzmann Method - M. Rizqie Arbie (Journal of Applied and Computational Mechanics, 2021)
Solid deposition in fluid may involve solids with different density and size and may happen in quiescent fluid or rather in counter flow. We perform a numerical investigation on the role of density-ratios, size-ratio, and initial configuration on the settling of two circular solids in a fluid channel with or without counter-flow. Through this study, we show how settling dynamics of two solids can be controlled. Numerical experiment based on a coupled Immersed Boundary-Lattice Boltzmann is employed. It is shown that certain parameter set leads to guided deposition while denser solid leaves the less dense one as time progressing. However, certain parameter set leads to periodic close encounters which is robust in the presence of Poiseuille-like counter-flow. In this case, the separation between two solids is bounded during the deposition.